Analysing Surface Heat Fluxes Variation with Imperviousness and Land Surface Temperature from Landsat Data - Bala R.; Yadav V.P.; Nagesh Kumar D.; Prasad R. (My University, 2025)
The research on spatial variation of surface heat fluxes is crucial to develop an understanding for urban heat island phenomena. This study aims to enhance the understanding of spatial pattern of energy fluxes and its variation with urbanisation. Thus, surface energy fluxes i.e. latent heat flux (LE), sensible heat flux (H) and artificial sensible heat flux (Has) were estimated by combined use of meteorological and Landsat satellite data for Bangalore city in India for years 2005, 2010, 2015 and 2020. Here, the ratio of heat flux with net radiation (Rn) was analysed for better comparison at different dates. The fluxes for each land cover type were estimated to investigate the spatial variability of energy fluxes. Compared to natural surfaces, the urban land cover had a lower mean LE/Rn and greater mean H/Rn and Has/Rn. The mean of LE/Rn decreased (0.304–0.168) and mean H/Rn (0.218–0.314) and Has/Rn (− 0.166 to − 0.072) increased from year 2005 to 2020 with urbanisation. Further, the correlation of fluxes with Impervious Surface Fraction (ISF) and land surface temperatures (LST) were analysed. LE/Rn showed negative association with ISF and positive with LST. H/Rn and Has/Rn showed positive correlation with ISF whereas negative with LST. The occurrence of urban cool island in Bangalore city resulted in this relation of H/Rn and Has/Rn with LST and ISF. Therefore, H/Rn was largely influenced with LST whereas LE/Rn is mainly dependent on the vegetation abundance and moisture conditions. © Indian Society of Remote Sensing 2024.